Comparing congratulatory speech in Javanese and Sundanese: influence of culture on strategies - Nofendralova, Shena Fiosa; Sartini, Ni Wayan (NOTION: Journal of Linguistics, Literature, and Culture, 2024)
While several expressive speech acts like requesting, apologizing, and inviting had been widely studied, the speech act of congratulating has been given little attention. This study compared how Javanese and Sundanese speakers congratulate each other, which has not been studied much before. This research also looked at how age, social power, and social distance affect the way people congratulate each other. The contribution of this paper lies in providing a nuanced understanding of how cultural and social values in Javanese and Sundanese societies shape congratulatory speech acts. The study involved 60 participants who completed a written Discourse Completion Task (DCT). A mixed-method approach combining quantitative and qualitative methods was used for analysis. The data was coded and categorized using Elwood’s (2004) framework. The study identified new strategies, such as mentioning occasion and divine remarks, that were significant in relation to the dataset. Participants responded to five real-life situations by providing congratulatory expressions in their local language on a Google Form. The most frequently utilized strategy is the expression of surprise which is followed by IFID in the second position. The presence of divine remarks in the act of congratulating in this study is attributed with the highly influence of Islamic culture in Indonesia. In terms of social position, social distance, and age, both groups demonstrate a preference for employing High variety (H) when interacting with individuals with higher position or older individuals.